A New Dihydroxanthenone from the Fermentation Products of Endophytic Fungus of Phomopsis amygdali - Li, Limei; Wang, Huan; Yang, Juanxia; Lou, Jie; Liu, Guiyou; Gao, Xuemei; Hu, Qiufen; Ye*, Yanqing (Asian Journal of Chemistry, 2014)
A new dihydroxanthone, (1R,2R)-2-hydroxy-6-(hydroxymethyl)-8-methoxy-9-oxo-2,9-dihydro-1H- xanthene-1-carboxylic acid (1) was isolated from the fermentation products of a Phomopsis fungus. Its structure was elucidated by spectroscopic methods. Compound 1 was tested for its cytotoxicity and it showed high cytotoxicity against NB4 and PC3 cell with IC50 values of 4.5 and 3.8 μM.